Morphologically derived adjectives in Spanish - Fábregas, Antonio (Issues in Hispanic and Lusophone linguistics ;, 2020)
"This is the first book that presents a complete empirical description and theoretical analysis of all major classes of derived adjectives in Spanish, both deverbal and denominal. The reader will find here both a detailed empirical description of the syntactic, morphological and semantic properties of derived adjectives in contemporary Spanish and a cohesive Neo-Constructionist analysis of the syntactic and semantic tools that contemporary Spanish has available to build adjectives from other grammatical categories within a Nanosyntactic-oriented framework. In doing so, this book throws light on the nature of adjectives as a grammatical categoy and argues that adjectives are syntactically built by recycling functional heads belonging to other categories. The book will be useful both to researchers in Spanish linguistics or theoretical morphology and to advanced students of Spanish interested in the main ways of building new adjectives through suffixation in this language"--